Mexico : Financial Sector Assessment Program Update; Detailed Assessment on the Implementation of the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2007)
The Detailed Assessment report on Mexico's implementation of the International Organization of Securities Commissions Objectives and Principles of Securities Regulation is analyzed. The Mexican securities market is dominated by daily trading in short-term government debt securities, primarily through repo transactions among banks, brokers, institutions, and private investors. The 2001 Financial Sector Assessment Program noted significant structural issues in the Mexican repo market, and recommended government action to create a standard master agreement for repo transactions.